The efficacy of kinesio taping versus forearm-band therapy in treating lateral epicondylitis: A prospective, single-blind, randomized, controlled clinical trial - Aykurt Karlıbel, İlknur; Kasapoğlu Aksoy, Meliha (Journal of Surgery and Medicine, 2022)
Background/Aim: The treatment of lateral epicondylitis (LE) is generally conservative, but evidence for its effects is insufficient. Although Kinesio Tape (KT) and forearm bandages (FB) are applied in the treatment of LE, the results regarding the effectiveness of these two treatment methods are controversial. Moreover, to our knowledge, no study compared these two methods with each other. Our aim was to investigate the effects of Kinesio Tape (KT) and forearm bandages (FB) on pain, tenderness, grip strength, function and quality of life and to compare these two methods. Methods: This study included 62 patients with LE diagnosis, between ages of 20 and 65. Patients were randomly assigned to one of two groups, representing KT (Group 1 = 31) and FB (Group 2 = 31), respectively. LE exercises were assigned as home programmes to both groups. Pain (VAS), the pressure pain thresholds (PPT), handgrip strength (HGS), the patient-rated tennis elbow evaluation (PRTEE), and the ‘Short Form-12’ evaluation parameters were used. Patients were evaluated at the beginning, third and sixth weeks. Results: Significant difference was not observed between two groups in terms of demographic data and baseline evaluation parameters (P>0.05). In group 1, a significant improvement was observed across all evaluation parameters at both the third and sixth weeks, except the PPT at the sixth week (P<0.05). Meanwhile, in group 2, a significant improvement was observed across all evaluation parameters except the PPT at the third week and the SF-12 mental component at the third and sixth weeks (P<0.05). No significant difference in evaluation-parameter scores was observed between the two groups at the third and sixth weeks (P>0.05) Conclusion: The KT and FB treatments significantly improve LE patients’ pain, handgrip strength, functions and quality of life. Moreover, neither method is superior to the other in this regard.